A Novel Normalized Cross-Correlation Speckle-Tracking Ultrasound Algorithm for the Evaluation of Diaphragm Deformation - Ye, Xiong; Liu, Zhi; Ma, Ying; Song, Ye; Hu, Lihua; Luo, Jianwen; Xiao, Hui (Frontiers in Medicine, 2021)
Objectives To develop a two-dimensional normalized cross-correlation (NCC) based ultrasonic speckle-tracking algorithm for right diaphragm deformation analysis. Methods Six healthy and eight mechanical ventilation patients were enrolled in this study. Images were acquired by a portable ultrasound system in three sections. DICOM data were processed with NCC to obtain the inter-frame/cumulative vertical and horizontal displacements, and global strain of the right diaphragm, with continuous tracking and drift correction. Results The NCC algorithm can track the contraction and relaxation of the right diaphragm follows the respiratory movement continuously. For all three sections, the inter-frame and accumulated horizontal displacements are both significantly larger than the corresponding vertical displacements (inter-frame p values: 0.031, 0.004, and 0.000; cumulative p values: 0.039, 0.001, and < 0.0001). For the global strains of the right diaphragm, there is no statistical significance found between every two sections (all p values > 0.05) whether the horizontal interval of the initial diaphragm point was 1, 3, 5, or 10 times in the sampling interval. Conclusions This study developed a novel diaphragmatic deformation ultrasound imaging method. This method can estimate the diaphragmatic inter-frame/ accumulated displacement in the horizontal and vertical direction and global strain at three different imaging planes, and it is found that the strain is not sensitive to the imaging plane.